2020
DOI: 10.1097/prs.0000000000006720
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Quality of Life for Women Undergoing Autologous versus Alloplastic Breast Reconstruction following Mastectomy: A Systematic Review and Meta-Analysis

Abstract: Breast cancer is recognized as the most frequently diagnosed cancer in female patients worldwide. 1 Surgical intervention including mastectomy is considered an integral part of and often is essential to favorable therapeutic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 34 publications
5
55
0
Order By: Relevance
“…To our knowledge we are the first paper to report PROMs data using an enhanced recovery protocol for microsurgical reconstruction. Our data compares favourably with the PROMS data reported in the UK national flap registry publication and a recent meta-analysis of international high volume institutions 3,25 . At a median of 11.6 months we found improvement across all domains in the BREAST-Q except for physical well-being with abdomen.…”
Section: Promssupporting
confidence: 74%
See 1 more Smart Citation
“…To our knowledge we are the first paper to report PROMs data using an enhanced recovery protocol for microsurgical reconstruction. Our data compares favourably with the PROMS data reported in the UK national flap registry publication and a recent meta-analysis of international high volume institutions 3,25 . At a median of 11.6 months we found improvement across all domains in the BREAST-Q except for physical well-being with abdomen.…”
Section: Promssupporting
confidence: 74%
“…Access to autologous reconstruction continues to be a challenge in the United Kingdom due to significant regional availability 1 . This is despite the wealth of evidence demonstrating its superiority over all other types of reconstruction in both the immediate and delayed setting 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…This was corrected for using Duval and Tweedie's trim-and-fill procedure to eliminate the effect of publication bias, yielding a reduced overall RR for delayed healing of 1.27, though it still remained significant (random 95% CI [1.00; 1.61];of 4%) (►Figs. 2,3). No other complication demonstrated publication bias (►Appendix D, available in the online version).…”
Section: Overall Patient Outcomesmentioning
confidence: 94%
“…Abdominally based free tissue transfer is considered by many to represent the gold standard for breast reconstruction following mastectomy, with patient-reported outcomes demonstrating improved long-term satisfaction as compared with alloplastic reconstruction. [1][2][3] Unfortunately, many patients may not be candidates for free tissue transfer as a result of medical comorbidities that may preclude the lengthy operation and recovery period following surgery. In addition, the abdominal donor site must fulfill certain criteria to be considered appropriate for use in reconstruction.…”
mentioning
confidence: 99%
“…A significant question raised is which breast reconstruction technique improves more individual quality of life and achieves satisfaction as measured with a patient-reported outcome. Eltahir et al [32, 33] recently reported that autologous breast reconstruction had superior outcomes compared with alloplastic breast reconstruction as measured by the BREAST-Q, despite the lack of RCTs presented. As expected, patients undergoing autologous breast reconstruction scored higher on almost all BREAST-Q scales compared with alloplastic breast reconstruction, while interestingly the greatest difference was observed in satisfaction with breasts [32, 33].…”
Section: Autologous Versus Alloplastic Breast Reconstruction (Prepectoral Vs Subpectoral Approach) – Complicationsmentioning
confidence: 99%